Effects of grinding corn through a 2-, 3-, or 4-high roller mill on milling characteristics, and finishing pig growth performance and carcass characteristics - Gebhardt, J. T.; Tokach, Michael D.; Woodworth, Jason C.; DeRouchey, Joel M.; Goodband, Robert D.; Coble, K. F.; Stark, Charles R.; Jones, Cassandra K.; Dritz, Steven S. (My University, 2016)
Finishing pigs (n = 922, initial BW = 40.1 kg) were used in a 97-d experiment to determine the effects of grinding corn through various roller mill configurations on milling characteristics and growth performance and carcass characteristics of finishing pigs in a commercial setting. Pens were randomly allotted to 1 of 4 experimental treatments by initial BW with 11 pens/treatment and 21 pigs/pen. All diets were fed in 5 phases with the same corn-soybean meal-based diets containing 20% dried distiller’s grains with solubles. Experimental treatments included corn ground to 685 µm using 2 sets of rolls (2-high), corn ground to 577 µm using 3 sets of rolls (3-high), corn ground to 360 µm using 4 sets of rolls in a fine grind configuration (4-high fine), and corn ground to 466 µm using 4 sets of rolls in a coarse grind configuration (4-high coarse). The same roller mill was used for all configurations with the appropriate lower rolls completely open when using 2 or 3 sets of rolls. Grinding rate (tonnes/hour) was greatest (P < 0.05) for the 2-high and 4-high coarse configurations followed by the 3-high configuration and lowest for the 4-high fine configuration. Electricity cost was lowest (P < 0.05) per tonne of ground corn for the 2-high configuration and was greatest for the 4-high fine configuration. Pigs fed diets containing corn ground with the 2-high configuration had the greatest (P < 0.05) ADFI and ADG with pigs fed diets with corn ground using the 4-high fine configuration having the poorest ADFI and ADG (2.81, 2.73, 2.65, 2.73 kg for ADFI and 0.987, 0.967, 0.940, 0.971 kg for ADG for 2-high, 3-high, 4-high fine, 4-high coarse, respectively). There were no differences in G:F, caloric efficiency, or carcass characteristics among pigs fed diets ground with the different roller mill configurations. Feed cost/kg gain was lowest (P < 0.05) for the 4-high coarse configuration and revenue/pig was greatest (P < 0.05) for the 2-high and 4-high coarse configurations. Income over feed cost (IOFC) was lowest (P < 0.05) for pigs fed diets with corn ground using the 4-high fine configuration; however, there were no differences in IOFC among the other milling configurations. In our study, roller mill configuration had a significant impact on grinding electricity cost, grinding rate, as well as ADFI and ADG; however, roller mill configuration had no impact on G:F.
Citation: Gebhardt, J. T., Tokach, M. D., Woodworth, J. C., DeRouchey, J. M., Goodband, R. D., Coble, K. F., . . . Dritz, S. S. (2016). Effects of grinding corn through a 2-, 3-, or 4-high roller mill on milling characteristics, and finishing pig growth performance and carcass characteristics. Journal of Animal Science, 94, 59-59. doi:10.2527/msasas2016-126
Keywords: Finishing Pigs; Grinding Cost; Roller Mill; Agriculture